The Influence of Digital Marketing and Business Management Knowledge on the Sustainability of MSME Marketing in West Sumatra - Aisyah, Hesty; Azizah, Nur; Farhan, Muhamad (Journal of Management, 2025)
This research analyzes the impact of digital marketing and business management knowledge on the marketing sustainability of micro, small and medium enterprises (MSMEs) in West Sumatra. Through empirical analysis, this research shows that there is a significant and positive relationship between digital marketing, business management knowledge and marketing sustainability. These findings highlight the important role of digital marketing strategies and knowledge sharing practices in enhancing MSMEs' market presence, customer engagement and overall marketing sustainability. The practical implications for MSMEs include integrating these strategies into their operational activities and investing in training activities for employees. As MSMEs in West Sumatra face an increasingly competitive business landscape, this research provides actionable insights to drive long-term success and resilience of MSMEs.